Innocent bystanders: developing countries and the war on drugs - Keefer, Philip; Loayza, Norman (World Bank, 2010)
Drug prohibition and developing countries : uncertain benefits, certain costs / Philip Keefer, Norman Loayza, and Rodrigo R. Soares -- The historical foundations of the narcotic drug control regime / Julia Buxton -- Can production and trafficking of illicit drugs be reduced or only shifted? / Peter Reuter -- Evaluating Plan Colombia / Daniel Mejía -- Evo, Pablo, Tony, Diego, and Sonny : general equilibrium analysis of the market for illegal drugs / Rómulo A. Chumacero -- Competitive advantages in the production and trafficking of coca-cocaine and opium-heroin in Afghanistan and the Andean countries / Francisco E. Thoumi -- Cocaine production and trafficking : what do we know? / Daniel Mejía and Carlos Esteban Posada -- Responding to the challenge of Afghanistan's opium economy : development lessons and policy implications / William A. Byrd